Optimized Extraction of High-Purity Pectin From Orange Biowaste using Synergistic Ultrasound-Microwave-Assisted Green Technologies. - MALPARTIDA YAPIAS, RAFAEL JULIAN; ARECHE, FRANKLIN ORE; DE LA CRUZ CALDERÓN, GINA; YATA-FRANCO, LESLY EDITH; TOCTO-YAJAHUANCA, LAUMER; CANCHARI FIERRO, YOSELYN ERIKA; COCHACHI POMA, WILLIAM ALBERTO; RUIZ RODRIGUEZ, ALFONSO (Current Research in Nutrition & Food Science, 2025)
Steady extraction methods need improvement to obtain pure pectin from citrus biowaste while enabling environmental waste management and advancing green manufacturing systems. Specifically, ultrasound cavitation will enhance mass transfer and microwave irradiation will provide rapid and uniform heating, leading to more efficient pectin extraction with improved functional properties. A full factorial experimental design (2³) was employed, analyzing the effects of three independent variables: temperature (°C), microwave power (W), and ultrasonic amplitude (%), on both pectin yield and its quality parameters, such as degree of esterification and sugar composition. Statistical validation was performed using ANOVA and Tukey's post-hoc test to confirm significant differences among treatments. Under optimal conditions (60°C and 500 W with 50% amplitude and 3 min duration), the pectin extraction process achieved a maximum yield of 65.40% (p < 0.001, η² = 0.961, 95% CI: (59.88%, 63.37%)). The derived pectin exhibited exceptional physicochemical attributes, including 78.67% (p < 0.001, η² = 0.954, 95% CI: (69.5%, 79.1%)) anhydrouronic acid, 81.56% (p < 0.001, η² = 0.950, 95% CI: (71.8%, 81.6%)), galacturonic acid content, and a 70.48% (p < 0.001, η² = 0.948, 95% CI: (61.8%, 70.2%)) degree of esterification, qualifying it as high-methoxyl class pectin with superior gelling and emulsifying properties. UMAE resulted in improved performance indicators, such as a water holding capacity of 11.01 g/g (p < 0.001, η² = 0.996), an oil holding capacity of 5.42 g/g (p < 0.001, η² = 0.990), an emulsifying activity index of 65.40%, and foam stability of 93.25%. Additionally, the method reduced overall extraction time by 70% (p < 0.001, η² = 0.970) and energy usage by 38.84% (p < 0.001, η² = 0.967), significantly contributing to sustainable production. While UMAE demonstrates improvements in extraction time and energy efficiency, claims of sustainability require further validation through life cycle analysis (LCA) and techno-economic assessments. These analyses would help quantify the environmental and economic impact of UMAE at an industrial scale.